Development and Validation of an Instrument for Assessing Distance Education Learning Environments in Higher Education: The Distance Education Learning Environments Survey (DELES) - Walker, Scott L. (Curtin University, 2003)
Globally, as distance education has become firmly embedded as a part of the higher education landscape, governments and institutions are calling for meaningful research on distance education. This study involved designing, developing and validating a learning environment survey instrument for use in distance education-delivered courses in post-secondary education. Specifically it involved merging two distinctive areas of study: psychosocial learning environments research and distance education research. The unique social structure of asynchronous distance education learning environments requires a unique and economical instrument for measuring the perceptions of distance education course participants. The research followed a three-stage instrument-development process of identifying salient scales, developing survey items, and field testing and analysing data using item analysis and validation procedures. This was followed by an investigation into the associations between the psychosocial learning environment and students enjoyment of distance education. The results yielded a new six-scale, 34-item Web-based learning environment instrument suitable for use in a number of asynchronous post-secondary distance education environments. The new instrument, the Distance Education Learning Environment Survey (DELES) assesses Instructor Support, Student Interaction and Collaboration, Personal Relevance, Authentic Learning, Active Learning, and Student Autonomy. Analyses of data obtained from 680 subjects supported the factorial validity and internal consistency reliability. The results also indicated statistically significant associations between the distance education learning environment and student enjoyment of distance education.